2020
DOI: 10.21272/mmi.2020.2-09
|View full text |Cite
|
Sign up to set email alerts
|

The Future of TV Advertising Targeting Young Slovak Consumers

Abstract: The consumer preferences and behavior should be considered with the purpose to implement marketing strategies in today's world successfully. It is crucial to understand how consumers find information and how the consumer decision-making process develops in time. Therefore, for advertisers, considering the behavior of their target audience is of paramount importance. Integrated marketing communication programs reflect the way online search and traditional and new media, such as smartphones, TV, and social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…At the same time, older people are more annoyed by advertisements than younger people. However, according to authors Miklošík, Starchon, Vokounová, Korcoková [40] the younger generation considers TV advertisements to be more annoying, which is why they tend to avoid the medium. Advertisements on television are considered to be a costly form of promotion, with the disadvantage of one-way interaction with the customer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, older people are more annoyed by advertisements than younger people. However, according to authors Miklošík, Starchon, Vokounová, Korcoková [40] the younger generation considers TV advertisements to be more annoying, which is why they tend to avoid the medium. Advertisements on television are considered to be a costly form of promotion, with the disadvantage of one-way interaction with the customer.…”
Section: Discussionmentioning
confidence: 99%
“…According to Efstathiou [39], traditional media are used for branding, and to action a sales promotion to drive revenue generation and profitability. Despite this, TV advertising is considered to have little influence on the customers; although it has been proven, that if it captures their attention, it can trigger further information research, often leading to a purchase decision [40]. Results of the study by Efstathiou indicated that radio advertising has the most significant influence on the customers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research on Slovakia students reveals that it still can be beneficial to include television advertisements in the communication mix aimed at these young consumers. To set all communication channels so that a brand in a TV advertisement can be considered in the consumer decision-making process consumer behavior need to be understood (Miklosik et al, 2020).…”
Section: The Use Of Marketing In the Context Of Different Age Consumersmentioning
confidence: 99%
“…Literature Review. Companies usually invest large amounts of funds to support marketing activities to support the company's image as an incentive to customers to making a purchase (Mura, 2020;Miklosik et al, 2020;Fedorko and Kakalejcik, 2015;Leboff, 2011;Keh et al, 2006). Smaizien and Jucevicius (2009) argue that companies choose to spotlight the image and omit their reputation.…”
mentioning
confidence: 99%